Inside Cover: A Modulator‐Induced Defect‐Formation Strategy to Hierarchically Porous Metal–Organic Frameworks with High Stability (Angew. Chem. Int. Ed. 2/2017). Issue 2 (21st December 2016) - Cai, Guorui; Jiang, Hai‐Long
Abstract : Pore size expansion and framework stability are two crucial issues, but are rarely addressed simultaneously in a single metal–organic framework (MOFs). H.‐L. Jiang and G. Cai show in their Communication onpage 567 ff. that a versatile modulator‐induced defect‐formation strategy allows the preparation of hierarchically porous MOFs (HP‐MOFs) with high stability and tailorable pore features, which enable HP‐MOFs to be important porous platforms for applications involving large molecules, especially in catalysis.